2020
DOI: 10.3389/fnagi.2020.542421
|View full text |Cite
|
Sign up to set email alerts
|

Surgery, Anesthesia and Intensive Care Environment Induce Delirium-Like Behaviors and Impairment of Synaptic Function-Related Gene Expression in Aged Mice

Abstract: To establish a clinically relevant mouse model of perioperative delirium. Methods: Aged C57BL/6J mice were tested at baseline in the Y-maze novel arm preference, buried food, simple discrimination task of the attentional set-shifting test, and open field tests. They were subsequently randomized to insult (anesthesia, surgery, and Intensive Care Unit environment) or control group. Insult-exposed mice received laparotomy under sevoflurane anesthesia, propofol sedation and exposure to intermittent lights, sounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 69 publications
0
34
0
Order By: Relevance
“…Witteveen et al assessed an ICU-AW model using in vivo strength measurements and myosin/actin assays in an Escherichia coli septic peritonitis mouse model [ 27 ]. Illendula et al reported that surgery, anesthesia, and an intensive care environment impaired mouse behaviors involving attention, memory, and thought organization, which allowed for the establishment of a clinically relevant mouse model of perioperative delirium [ 28 ]. These models revealed human-like PICS symptoms; however, neither mouse model was intubated or ventilated.…”
Section: Discussionmentioning
confidence: 99%
“…Witteveen et al assessed an ICU-AW model using in vivo strength measurements and myosin/actin assays in an Escherichia coli septic peritonitis mouse model [ 27 ]. Illendula et al reported that surgery, anesthesia, and an intensive care environment impaired mouse behaviors involving attention, memory, and thought organization, which allowed for the establishment of a clinically relevant mouse model of perioperative delirium [ 28 ]. These models revealed human-like PICS symptoms; however, neither mouse model was intubated or ventilated.…”
Section: Discussionmentioning
confidence: 99%
“…Illendula et al used 18- to 20-month-old mice to examine anesthesia, surgery, and the intensive care unit environment and found that these insults impaired mouse behaviors that depend on attention, memory, and thought organization. The changes also showed acute onset and fluctuated over time (Illendula et al, 2020 ). Our research group also used a battery of behavioral tests to assess the effects of laparotomy under isoflurane anesthesia in aged mice and found that inattention, the core symptom of delirium, occurred at 6 or 9 h and recovered at 24 h after anesthesia/surgery (Liu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory mediator regulation of TRP channels, neuroactive ligand-receptor interaction and cholinergic synapse were overrepresented during the acute presence of hippocampal inflammation ( Xiang et al, 2019 ). Illendula et al (2020) found that many key proteins for the regulation of synaptic vesicle trafficking, neurotransmitter release and synaptic plasticity-were significantly down-regulated in old mice under surgery, anesthesia and intensive care environment induce delirium. Lipoprotein-associated phospholipase A2 and superoxide dismutase were independent risk factors of cognitive impairment in cerebral small vessel disease, and may be useful for the rapid evaluation of cognitive impairment in cerebral small vessel disease ( Zhu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%